A Theoretical Study of Surface Phenomena in the Selective Dissolution of Copper-Zinc Alloys - V.I. Pokhmurskii; V.I. Kopylets; M.S. Khoma (Adsorption Science & Technology)
A cluster model has been developed to explain the interaction of deformed metals in aggressive corrosion environments. Theoretical calculations have explained the selective dissolution of deformed brass in an acidic sodium chloride solution.